Influenced factors of information technology outsourcing decision for E-business adoption among Malaysian small medium enterprises - Sulaiman R.; Sabri S.M. (American Scientific Publishers, 2023)
Previous studies in E-Business showed that majority Small Medium Enterprises (SMEs) are still struggling to compete with the current business trend and emerging technology based business model. In Malaysia, SMEs represent nearly 99.2% of the registered companies and become major contributor to the countrys economic growth. However, the number of SMEs who are involved in e-Business are still at a small percentage. This research aims to look at SMEs awareness and readiness level to consider Information Technology (IT) outsourcing approach as one of the solutions to accelerate their e-Business adoption. Past studies in the IT outsourcing (ITO) area mostly focusing on large companies from different perspectives. Not many can be found on SMEs and e-Business adoption. To provide in-depth understanding on the current situation, case study method was used. Data for this study was collected through a series of interview with the SMEs and IT outsourcing providers. This paper presents the early findings of influence factors of IT outsourcing decisions which were obtained from the interviews and literature review. These factors will be further analyzed and will be used to construct a model to assist the SMEs in determining the required IT outsourcing services for their e-Business adoption. 2017 American Scientific Publishers All rights reserved.